Emergencies in Oncological Practice - Islam, Md Rafiqul (Bangladesh Journal of Medicine, 2023)
Oncological emergencies are defined as an acute lifethreatening event in a patient with a tumor occurring as part of their complex treatment regimen or secondarily to their underlying malignancy. These events can occur at any time from the initial diagnosis of their cancer to endstage disease; and can be encountered in any clinical setting, ranging from primary care physician and emergency department visits to a variety of subspecialty environments. Oncologic emergencies are clinical situations that can lead to death in a short time (24-48 hours) if not quickly faced. In the clinical practice of the medical oncologist, such situations do not infrequently occur. The onset of oncologic emergencies may depend on the presence of cancer itself, the therapies carried out to counteract cancer, or the patient’s predisposition to develop such events. It is essential to recognize the aforementioned situations early in order to treat them promptly, thus avoiding serious consequences. BJM Vol. 34 No. 2(1) Suppliment 2023 Scientific Presentation 186 Therefore, it is critically important that all physicians have a working knowledge of the potential oncological emergencies that may present in their practice and how to provide the most effective care without delay. Nervous system emergencies include spinal cord compression, raised ICP, leptomeningeal disease, seizures and altered mental status whereas superior venacaval syndrome, hyperviscocity syndrome, hyperleukocytosis, venous thromboembolism, Hemorrhage and DIC are the vascular and haematologic emergencies. Several classic metabolic oncologic emergencies include syndrome of inappropriate antidiuretic hormone secretion, tumor lysis syndrome and hypercalcemia of malignancy. Among the pulmonary problems airway obstruction, massive haemoptysis, toxic lung injuries, pneumonitis and pulmonary fibrosis can be caused by cancer and cancer treatment. Urologic emergencies such as hemorrhagic cystitis and obstructive uropathy are also seen. Gastrointestinal bleeding in patients with cancer and typlitis in patients with neutropenic fever are potentially serius complications also. Immune check point inhibitors may cause irAEs in practically any organ system ranging from SJS, TEN, thyroiditis, hypophysitis, adrenilitis, diabetic ketoacidosis to life threatening pneumonitis and myocarditis which may be associated with poor overall survival. Oncologic emergencies can threaten the well-being of almost any patient with a malignancy. Although some of these conditions are related to cancer therapy, they are by no means confined to the period of initial diagnosis and active treatment. In the setting of recurrent malignancy, these events can occur years after the surveillance of a cancer patient has been appropriately transferred from a medical oncologist to a primary care provider. As such, awareness of a patient’s cancer history and its possible complications forms an important part of any clinician’s knowledge base. Prompt identification of and intervention in these emergencies can prolong survival and improve quality of life, even in the setting of terminal illness. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 186-187